The characteristics and sanctioning of tackles during the 2011-2015 under 18 Craven Week rugby tournament - Boucher, S. J. (2017)
Rugby is one of the most popular team sports in the world, however, the high injury rate associated with it is an area of concern for coaches, players, parents and referees. The tackle is the most common contact event in the game and because of this accounts for the most injuries during training and matches. Due to the nature of the game the tackle event will always be present. Sport participation among children and adolescents is increasing globally, due to the many health related-benefits attributable to engaging in sport including enjoyment, social interaction and health. Research into schoolboy rugby tackle characteristics is limited and even less is known regarding the sanctioning of illegal tackles by the referees during match-play, particularly in South Africa. The primary aim of the study was to determine the number of illegal tackles and if they were sanctioned or not sanctioned by the referee`s during the 2011- 2015 under 18 Craven Week tournaments. The secondary aim was to assess which factors were associated with sanctioning and non-sanctioning of illegal tackles. This thesis followed a research article format, with the specific aims being investigated in each article. Research article one assessed the legal and illegal tackles characteristics during the 2011-2015 under 18 Craven Week tournament. Research article two focused on the sanctioning and non-sanctioning of illegal rugby tackles during the 2011-2015 under 18 Craven Week tournament. Research article one revealed an average of 123 tackles per match. The tackles were spread evenly throughout the four quarters of the match. Most of the tackles occurred front-on (65%) which is consistent with other literature. Also in agreement with other literature was the finding that most tackle events involved one tackler (66%). The study revealed that 12103 (99%) tackles were deemed legal and only 113 (1%) tackles were found to be illegal, as judged by the coding of the match videos. Most of these occurred front-on (66%) and involved one tackler (91%). Most of the illegal tackles took place in quarter two (29%) and four (29%) of the match, which highlights the effect of fatigue, leading to poorer tackling technique and decision making by the tackler. The second research article revealed 113 illegal tackles, of which 46 tackles were sanctioned and 67 tackles were non-sanctioned by the referee. The high tackle (72%) being the most common type of illegal tackle. Most of the illegal tackles took place in quarter two (29%) and four (29%). Illegal tackles mainly took place front-on (66%) and involved one tackler (91%). Most illegal tackles (59%) were not sanctioned by the referees, especially in 2012 (84%). A high percentage of high tackles (65%) and dangerous charging tackles (67%) were not sanctioned by the referee. This is an area of concern for players, coaches and referees as illegal tackles have the highest propensity for injury in comparison to any other contact event. Full understanding of the characteristics surrounding the tackle and sanctioning of illegal tackles is the initial step in the injury prevention model. This information will guide the rugby education programmes into what law, technique and coaching changes need to be put in place in order to make rugby safer across all level of play. Strict enforcement of the laws by referees will help make the game safer for all involved.